The Effect of Perception of Ease of Use and Perception of Benefits on Go-food Customer Purchase Interest During The Covid-19 Pandemic in Malang City - Dinda Desy Kurnia Putri; Eko Handayanto; Noor Aziz (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2022)
This study aims to examine the effect of perceived ease of use and perceived benefits on the purchase intention of Go-food service user students in Malang City during the Covid-19 pandemic period. This study uses the theory of the Technology Acceptance Model (TAM). The population in this study were all Go-food service users in the city of Malang during the Covid-19 pandemic. The number of samples used was 100 respondents. Sampling technique using Non-Probability Sampling with Accidental Sampling. Data collection techniques using online questionnaires. The data analysis technique used multiple linear regression. The results showed that: 1) Partially perceived ease of use had a positive and insignificant effect on purchase intention, 2) Partially perceived benefits had a positive and significant effect on purchase intention, 3) Simultaneously, perceived ease of use and perceived benefits had a positive and significant effect on purchase interest.